Covid-19 Airway Management and Ventilation Strategy for Critically Ill Older Patients - Vargas, Nicola; Esquinas, Antonio M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This book describes the issues and challenges that clinicians encountered in the management of older critically ill patients during the Covid-19 pandemic, and offers practical information on how to manage them. Older adults are more susceptible to complications such as acute respiratory distress syndrome (ARDS) as a result of viral pneumonia. In addition, they often have multiple comorbidities and are commonly frail, which means their various organs and systems, such as the respiratory system, have reduced functional reserves. As such, older adults are less able to react to acute stressors. During the current Covid-19 pandemic, older adult patients' mortality is increased. Further, the infection and death rates of elderly people in nursing homes and health care institutions are high. Management of older adults with Covid is complicated. The reduced availability of beds may limit their access to ICU. Moreover, the prognosis may be poor, and airway management and ventilation strategies have to take into account various clinical and physiological characteristics specific to older patients. This book is addressed to all allied professionals involved in the management of older critically ill patients and presents information collected and practical lessons learned from the clinical daily management of this population during the pandemic. .
Part 1. Epidemiology -- Chapter 1. Mortality and prognosis of older patients during COVID-19 pandemic -- Chapter 2. Elderly pneumonia COVID 19 cases : impact on the outcome -- Chapter 3. Incidence of ARF due to COVID 19 interstitial pneumonia -- Chapter 4. Changing the demographics in ICU Touring the Covid 19 pandemic -- Part 2. The diagnosis of COVID ARF in Elderly -- Chapter 5. Differential Diagnosis of Types of Pneumonia in the Elderly -- Chapter 6. The diagnosis of COVID ARF in Elderly: the radiological findings in elderly -- Part 3. The screening and the access to ICU -- Chapter 7. The screening and the access to ICU -- Chapter 8. The decision - making process of selection in the clinical pathway for COVID 19: the recommendations for older patients -- Chapter 9. COVID-19: End of life care decision making and preferences in older people -- Part 4. Management of ARF -- Chapter 10. The impact frailty, comorbidity and ageing of the respiratory system on the unfavourable prognosis of COVID 19 -- Chapter 11. THE PHYSIOPATHOLOGY OF COVID ACUTE RESPIRATORY FAILURE -- Chapter 12. Escalation therapy for ARF in elderly patient -- Chapter 13. Oxygen Therapy : liberal versus conservative in older patients with COVID disease -- Chapter 14. The role of non-invasive ventilation -- Chapter 15. The invasive ventilation in older patients: the timing -- Chapter 16. The role of ECMO -- Chapter 17. The role of HFNC -- Chapter 18. The Problem of Aerosolization -- Part 5. The setting -- Chapter 19. The older patients in Subacute Units -- Chapter 20. The ICU -- Chapter 21. The admission of older patients with COVID 19 in the general wards -- Chapter 22. The management of elderly patients with Covid out of the Hospital: the Italian experience -- Part 6. Conclusion -- Chapter 23. The geriatric perspectives in the time of COVID 19.
Keywords: Critical care medicine; Geriatrics; Emergency medicine; Respiratory organs$1 (BDiseases.s; Intensive / Critical Care Medicine; Geriatrics/Gerontology.; Emergency Medicine; Pneumology/Respiratory System